2018
DOI: 10.2134/jeq2017.07.0294
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Regional Effects of Climate Change on Soil Organic Carbon in Spain

Abstract: Soil organic C (SOC) stock assessments at the regional scale under climate change scenarios are of paramount importance in implementing soil management practices to mitigate climate change. In this study, we estimated the changes in SOC sequestration under climate change conditions in agricultural land in Spain using the RothC model at the regional level. Four Intergovernmental Panel on Climate Change (IPCC) climate change scenarios (CGCM2-A2, CGCM2-B2, ECHAM4-A2, and ECHAM4-B2) were used to simulate SOC chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…The authors of Reference [16] also stated that future climatic scenarios can decrease SOC stocks in the upper sections of the soil profile when rainfall decreases as compared to increases in deeper layers. Jebari et al [8] also using the RothC model, predicted that SOC content will decrease in the different climate change scenarios in comparison with no climate change scenario for future decades overall Spain. In our study, simulations of the SOC in the rangeland of BandBast area in Ghir-O-Karzin are in agreement with the aforementioned research results since SOC decreases under climate change conditions were predicted by the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of Reference [16] also stated that future climatic scenarios can decrease SOC stocks in the upper sections of the soil profile when rainfall decreases as compared to increases in deeper layers. Jebari et al [8] also using the RothC model, predicted that SOC content will decrease in the different climate change scenarios in comparison with no climate change scenario for future decades overall Spain. In our study, simulations of the SOC in the rangeland of BandBast area in Ghir-O-Karzin are in agreement with the aforementioned research results since SOC decreases under climate change conditions were predicted by the model.…”
Section: Discussionmentioning
confidence: 99%
“…Climate factors such as precipitation and temperature have a significant effect on SOC contents which is the basic component of the global carbon cycle, particularly in the context of climate change [7][8][9][10][11]. Most researchers [10,[12][13][14] have reported losses from the soil organic carbon under the climate change conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Under Mediterranean conditions, characterised by seasonal dryness due to hot-dry summers and mild-wet winters, several authors have observed lower SOC levels than in temperate areas (Aguilera et al, 2013;Chiti et al, 2012), and have remarked on the difficulty of increasing SOC due to the rapid mineralisation and low humification rates under hyper-thermic conditions (Gervois et al, 2008). Several studies have reported national or regional SOC stocks under these Mediterranean conditions (Álvaro-Fuentes et al, 2008;Doblas-Miranda et al, 2013;Muñoz-Rojas et al, 2012;Rodríguez Martín et al, 2016), with some simulations made about the possible climate change effect on lowering SOC levels (Jebari et al, 2018;Pardo et al, 2016). However, information on the tendencies of these SOC stocks based on real situations through different temporal soil samplings is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (Smith et al, 2008) support the notion that soil C sequestration represents 89% of the potential of agricultural GGE mitigation. This effect can be even stronger under Mediterranean conditions, where SOC levels are low (Gil et al, 2018;Jiménez-Ballesta et al, 2012;Rodríguez Martín et al, 2016), although such losses could be limited by soil management and climate changes (Jebari et al, 2018). The main goals of this study were to: i) determine the SOCS on the Majorca island; ii) analyse the spatial variability of soil organic carbon in relation to the influence of human activities and land use; iii) assess the temporal changes in soil organic carbon in agricultural soils after 10 years by setting the island as an exploratory plot to know the translatable tendencies for Mediterranean areas.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that diversified rotations will be more resilient and SOC could increase under the impacts of future climate change compared with CC or CCSS rotations. Jebari et al (2018) estimated the changes in SOC at the regional level under climate change conditions in agricultural land in Spain using the RothC model. Four different Intergovernmental Panel on Climate Change (IPCC) scenarios (CGCM2-A2, CGCM2-B2, ECHAM4-A2, and ECHAM4-B2) were used to simulate SOC changes during 2010 to 2100.…”
Section: Process-based Models To Evaluate Soil Organic Carbon Dynamicsmentioning
confidence: 99%